2016
DOI: 10.3233/jad-151193
|View full text |Cite
|
Sign up to set email alerts
|

Reelin in Alzheimer’s Disease, Increased Levels but Impaired Signaling: When More is Less

Abstract: In the continuing search for proteins that play a role in Alzheimer's disease (AD) and that are related to the pathological hallmarks, those that influence cognitive function and that constitute potential therapeutic targets deserve special interest. Reelin is a signaling protein that is involved in a cascade of cytoplasmic events that control tau phosphorylation and that regulate synaptic neurotransmission, plasticity, and memory. Both Reelin expression and glycosylation are modulated by amyloid-β (Aβ), sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 143 publications
2
23
1
Order By: Relevance
“…Another consequence of the lesser reelin levels in AD-ApoE4 carriers is the difficulty of interpreting altered reelin expression in various AD cohorts if the APOE genotype is not investigated. Although we previously found increased reelin associated to AD in various cohorts, we also noted large intersubject variability in reelin protein and mRNA levels, and reports from other laboratories have been controversial regarding reelin changes in AD; now, in the light of our results, these differences could be explained by the presence or lack of the APOE-e4 allele (discussed in Cuchillo-Ibañez et al 43).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Another consequence of the lesser reelin levels in AD-ApoE4 carriers is the difficulty of interpreting altered reelin expression in various AD cohorts if the APOE genotype is not investigated. Although we previously found increased reelin associated to AD in various cohorts, we also noted large intersubject variability in reelin protein and mRNA levels, and reports from other laboratories have been controversial regarding reelin changes in AD; now, in the light of our results, these differences could be explained by the presence or lack of the APOE-e4 allele (discussed in Cuchillo-Ibañez et al 43).…”
Section: Discussionsupporting
confidence: 45%
“…Alterations in reelin levels can contribute to the progression of AD pathology (49) and probably affect the capacity of reelin to protect against Ab toxicity (50,51). The crosstalk between APP/Ab and reelin has been shown by various groups, but the effect of Ab on reelin function should be considered when interpreting changes in expression in AD (discussed in Cuchillo-Ibañez et al 43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fact that children with autism display a large increase in reelin monomers levels after denaturation suggests the existence of a higher proportion of reelin dimers/oligomers in the plasma of these children with regards to non-ASD children. Differences in reelin complexes have been reported in other neurological condition such as Alzheimer's disease (29,30). Remarkably, recent data indicate that commercial anti-reelin antibodies display different reactivity to monomeric or dimeric reelin protein (31), which highlights the relevance of an appropriate methodological design for reelin quantitative analyses.…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, insufficient Reelin signaling could contribute to the pathogenesis of neuropsychiatric disorders, such as epilepsy [17][18][19] , schizophrenia 6,16,20 , and autism 3,8,16 . Furthermore, recent studies showed that a decrease or insufficiency in Reelin signaling could aggravate Alzheimer's disease (AD) 13,[21][22][23][24][25][26] . Therefore, it is important to understand the molecular mechanisms by which Reelin is regulated.…”
Section: Introductionmentioning
confidence: 99%